Man more Animal than Anything: The Unity in Human Agency - Finley, John (New blackfriars, 2019)
Owen Flanagan takes his claim that ‘we are animals through and through’ to imply ‘our animal side is our only side’. But ‘Cartesianism’ is not the only alternative available: Aquinas’ view of the human soul as a spiritual reality that is essentially the form of the body means that animality characterizes humans in an especially intimate way. Aquinas recognizes degrees of unity. Homogeneous inanimate substances have an accidental unity; living organisms are essentially one: the self pervades the whole, and the form is closely related to this particular matter. The human soul communicates to the body the being the soul possesses, hence it is more intimate to the body than any bodily quality, while the body is more intimate to the soul than any of the soul's powers. In isolation from the body the soul cannot exercise its own proper activity, which is to know sensible reality. This high degree of metaphysical unity is manifest at the level of action and experience. Robert Sokolowski's account of speech as a defining feature of human beings illustrates how bodiliness is needed for the soul's intellectual activity. Syntactical speech is formed by and expressive of intelligence as embodied and temporally conditioned. The human being's superior ontological unity is not refuted by experiences of disintegration. Our soul, in its simplicity, needs to originate a unique gamut of powers; hence the human being can go wrong in many ways. The tension among our powers is experienced acutely because it is within the one soul. Human death is not really unnatural, but is more violent than in the case of the other animals. However, as a final mortification it allows us to offer our selves in conformity to Christ.